Conseil Constitutionnel (2021-821 DC, 29 JULY 2021). Recherches sur l’embryon, droit, éthique (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In this decision on 29th July 2021, the French Constitutional Council declares in conformity with the Constitution the innovations instituted by the legislator: the right to carry out research for improving knowledge of human biology, the right to create transgenic or chimeric embryos. The Constitutional Council adopts a self-restraint position, granting the legislator ample discretionary freedom in terms of ethical choices. This decision is important since it allows to reflect both on the status of the embryo with regard to free scientific research and on the principle of human dignity.
Keywords: human embryo; freedom of scientific research; human dignity; enhancement; gene editing